Fund Concessional Financial Support For Low-Income Countries-Responding To The Pandemic. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2021)
This paper proposes a package of policy reforms and a funding strategy to ensure that the Fund has the capacity to respond flexibly to LICs' needs during the pandemic and recovery. The key policy reforms proposed include: -- raising the normal annual/cumulative limits on access to PRGT resources to 145/435 percent of quota, the same thresholds for normal access in the GRA; -- eliminating the hard limits on exceptional access (EA) to PRGT resources for the poorest LICs, enabling them to obtain all financing on concessional terms if the EA criteria are met; -- changes to the framework for blending concessional and non-concessional resources to make it more robust and less complex; -- stronger safeguards to address concerns regarding debt sustainability and capacity to repay the Fund; and -- retaining zero interest rates on PRGT loans, consistent with the established rules for setting these interest rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Health Behavior; Monetary Policy; Political Economy